Pengaruh Harga, Store Atmsophere dan Gaya Hidup terhadap Keputusan Pembelian di Benu Coffee and Roastery Cabang Medan - Andini Arianti; Sari Wulandari (Jurnal Bisnis, Manajemen, dan Akuntansi, 2022)
This study aims to determine the influence of price, store atmosphere and lifestyle on purchasing decisions in Benu Coffee And Roastery Cabang Medan. Data analysis techniques that researchers use in this research is descriptive quantitative. The sample in this study are consumers at Benu Coffee And Roastery Cabang Medan, totaling 99 people. The results of this study obtained a linear regression equation multiple Y = 19,545 + 0,033 X1 + 0,901 X2 + (-,147) + e. the test result partially show that the price of has a value of tcount (0,226) < nilai ttable (1,291) with a significant value of 0,821, it can be stated that the price variable has no positive and significant effect on purchasing decisions. Store atmosphere has a value of tcount (6,064) > nilai ttable (1,291) with a significant value 0,000, which means that there is an influence of store tmosphere against the purchase decision. Lifestyle has a value of tcount (-0,986) < nilai ttable (1,291) with a value of significant at 0,326, which means that there is no influence of lifestyle on purchasing decisions. Result F test shows that the value of Fcount sebesar 13,357 > Ftable 3,092with a value of sig 0,000 < 0,10. Test resultsproves that price, store atmosphere and lifestyle simultaneously have a positve and significant effect which means that the relationshp between price variables, store atmosphere and lifestyle on purchasing decisions is 54.3%. The R2 value of 0.295 means that purchasing decisions can be explained by the price variable, store atmosphere and lifestyle by 29,5% while the rest is explained by other factors which is not researched in this research. Keywords : Price, Store Atmosphere, Lifestyle, purchasing decisions